What News on the Rialto? Fundraising and Publicity for Operas in Seventeenth-Century Venice - Thorburn, Sandy (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2003)
Commercial operas of seventeenth-century Venice, the earliest public operas, are generally described as rigorously literary from 1637-1660. Various tools, including sets, machines, and musical forms helped audiences from various classes and places understand this Venetian Carnevale entertainment. The goal—to create a commercial entertainment industry that reflected and highlighted the wonders of Venice—was identified early in the history of Venetian commercial opera. This paper seeks to define the extent to which nascent commercial enterprises like newspapers, the mail, publishing, and advertising defined the content and nature of these early operatic works.